Increasing Organizational Commitment: Literature Review - Sutisna, Didi; Tukiran, Martinus (UNIVERSITAS PAKUAN, 2023)
This article aims to present a comprehensive literature review on the factors that influence the enhancement of organizational commitment. Organizational commitment is an important aspect of human resource and organizational psychology research, as it has significant implications for individual performance, organizational sustainability, and the achievement of organizational goals. The literature review was conducted by analysing the findings of relevant previous studies so that it is possible to systematically identify and present the variables that influence increased organizational commitment. Previous research has provided valuable insights into the factors that influence the enhancement of organizational commitment. However, there is still room for further research to explore and clarify the relationship between these variables and organizational commitment. The proposed constellation model by including demographic factors as moderator variables is expected to be material for further research so that the influence of demographic factors as moderators between the independent variables and the organizational commitment variable can be known. The proposed proposition is that the relationship between the Independent Variables and organizational commitment is moderated by Demographic Factors..